Living during COVID-19: qualitative analysis of Experts by Experience UK University Associates' socioeconomic inequalities, including readiness recommendations - Rooney, Joy M. (Frontiers in Public Health, 2025)
A vulnerable group of people with disabilities and carers (Experts by Experience) wished for research during the COVID-19 pandemic to assist other people with disabilities in the future. Consideration of this vulnerable group seems to be limited in future policy pandemic readiness despite huge potential mortality. Literature reviewed critical public health theory through assessing health inequalities and health equity in relation to disability/chronic ill health. A standard qualitative thematic method distinguished socioeconomic health inequalities for people with earlier mental/psychosocial distress and other Experts by Experience-including people with physical, visual, self-identified hidden disabilities, and their carers. Environmental, community, and individual challenge were part of the overarching theme. Up to five sub-themes were: shielding, diminished quality of life, use of social media vs. the digital divide, people with hidden disabilities, activism, celebrating lockdowns' ends, loss in stability of outlook, loneliness/isolation, coping strategies, developing new skills, re-evaluating lives because the world will change. Discussion of findings relied on four critical public health pillars; included were future recommendations for pandemic/emergency readiness.